Relationship between timed online exposure and musculoskeletal health during COVID pandemic in allied health science students - Mishra, Priyadarshini; Biswal, Pratyush Ranjan (International Journal Of Community Medicine And Public Health, 2021)
Background: Musculoskeletal issues have persistently growing for students of allied health sciences with the online classes during the coronavirus disease (COVID) pandemic. To find out the relationship between timed online exposure and musculoskeletal health of allied health sciences students even though having mere basic knowledge about the cause and its prevention. Methods: Students who attended online classes in allied health science colleges were given with online questionnaire and those who volunteered to participate were included. The standardized Nordic questionnaire was used with a demographic section and no of hour’s exposure to online classes. Results: The Nordic questionnaire for cervical spine and upper extremity in 7 days exposure was found to be significant statistically and the positive response for pain was 66.3%. Conclusions: Musculoskeletal problems increased with the increase in time in front of computers /mobile phones for long hours for their classes. Further initial exposure itself causes it.